Chippewa Squaw Making Birch Canoe - Ingersoll, T. W. (Truman Ward), 1862-1922 photographer. (William L. Clements Library, 1922)
Full length portrait of unidentified Ojibwa Indian woman wearing western clothing seated while constructing birch-bark canoe. Four other individuals appear in camp in background.; Photograph attributed to T. W. Ingersoll. Original negative likely produced approximately 1890 to 1900.; Printed on left-hand margin: Keystone View Company Manufacturers Publishers Copyrighted Made in U.S.A.; Printed on right-hand margin: Meadville, Pa., New York, N.Y., Portland, Oregon, London, Eng., Sydney, Aus.; Photograph description printed on verso.; "Copyright by The Keystone View Company"; Series number: 26.; Keystone View Company reference number: 20957.; Title derived from image caption.; "Ojibwa Indians" variant names: Anishinaabe, Chippewa Indians, Ojibwe Indians.